Strong, safe, and resilient : (The World Bank, 2013)
The World Bank supports countries around the world in mainstreaming a comprehensive and integrated approach to disaster risk management into development. The World Bank provides analytical and advisory services, helps to build climate and disaster resilience into core investments across sectors, and offers unique financial solutions to better manage the contingent fiscal risks from disasters.